Detailed phenotypic analysis of B-cell lymphoma using a panel of antibodies reactive in routinely fixed wax-embedded tissue. - Norton, A. J. (1987)
Sixty-three well characterized B-cell lymphomas, with diagnoses previously established by conventional cryostat immunocytochemistry or limited paraffin immunocytochemistry, were studied. The tumors encompassed most of the Kiel subtypes and included the newly recognized entity, sclerosing mediastinal B-cell lymphoma. by the avidin-biotin peroxidase complex technique, each tumor was stained with a panel of monoclonal and polyclonal antibodies reactive in routinely fixed wax-embedded tissues. The panel included four reagents recognizing probable T-cell and B-cell restricted leukocyte common moieties (UCHL1, MT1, MB1, 4KB5), three antibodies to B-cell-related antigens (KiB3, MB2, LN1), and one to a macrophage-related antigen (Mac411). Other antibodies employed included anti-mu chain, anti-kappa, anti-lambda, and seven antibodies to non-phenotype-associated antigens, including HLA-DR (TAL-1B5, LN3, LN2, MB3), CD15 (C3D-1), and CD30 (BER-H2). Monotypic surface or perinuclear space and cytoplasmic immunoglobulin were detected in 80% of cases. Distinctive immunocytochemical profiles were demonstrable in many tumor categories by means of the panel of antibodies, thus facilitating the differential diagnosis of tumors of similar morphology. These results, together with our work on T-cell lymphoma in paraffin sections, show that accurate phenotypic analysis of lymphoma is now possible in routinely processed tissues.